Tingkat Kesadaran dan Kesiapan Pelaku Umkm Dalam Menyusun Laporan Keuangan dan Pajak - Rachmawati, Nurul Aisyah; Ramayanti, Rizka; Setiawan, Rudi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2021)
This study aims to analyze the level of awareness and readiness of Micro, Small, and Medium Enterprises (MSMEs) in preparing financial and tax reports. Data used in this study is primary data, which was obtained from the survey in April-May 2021. The data obtained were analyzed using descriptive qualitative research methods. The results show that the level of awareness and readiness of MSMEs in preparing financial and tax reports is still relatively low. MSMEs with the support of regulators need to make extra efforts to minimize the obstacles faced when compiling financial and tax reports.